Cities in Kalimantan in the Short Story “Kota-kota Air Membelakangi Air” by Raudal Tanjung Banua - Septian Rifki Sugiarto; Eta Farmacelia Nurulhady; Sukarjo Waluyo (SUAR BETANG, 2023)
The city and its people are not free from the problems that surround them. Moreover, for cities that depend a lot for their continuity and life on nature, for example, the water sector. As time progresses, these cities often begin to abandon the way of life they have lived for a long time. Such a picture is depicted in the short “Kota-Kota Air Membelakangi Air” (The water cities are rejecting the water) by Raudal Tanjung Banua. These various problems certainly did not arise suddenly without a reason behind them. This article tries to look at the picture of cities in Kalimantan, past and present, which seem to have changed a lot. To uncover this problem, the author uses a literary sociology approach and the theory of social change. The analysis carried out is based on the interpretation of the objectives, which is then supported by various related references. The results show that there have been social changes in people's lives in various cities in Kalimantan. The majority of people live in the water sector. As a result, cities in Kalimantan that used to live in the water sector began to recede and die. An indication that there has been social and cultural change in society in various cities in Kalimantan. This is caused by various factors, such as modernization and industrialization, which have a direct impact on changes in the physical environment, changes in population, attitudes and values, and needs that are deemed necessary.AbstractKota beserta masyarakatnya tidak lepas dari problematika yang melingkupinya. Terlebih, bagi kota-kota yang banyak menggantungkan kelangsungan dan kehidupannya terhadap alam, misalnya sektor perairan. Seiring perkembangan zaman, kota-kota tersebut acap mulai meninggalkan cara hidup yang telah dijalani sejak lama. Gambaran yang demikian terpotret dalam cerpen “Kota-Kota Air Membelakangi Air” karya Raudal Tanjung Banua. Berbagai persoalan tersebut pastinya tidak lahir secara serta-merta tanpa ada suatu sebab yang melatarbelakanginya. Tulisan ini mencoba melihat gambaran kota-kota di Kalimantan dulu dan sekarang yang tampak jauh telah berubah. Untuk mengungkap masalah tersebut, penulis menggunakan pendekatan sosiologi sastra dan teori perubahan sosial. Analisis yang dilakukan didasarkan pada interpretasi objektif, kemudian didukung oleh berbagai referensi terkait. Hasilnya menunjukkan bahwa telah terjadi pergeseran dan perubahan sosial dalam kehidupan masyarakat di berbagai kota di Kalimantan. Mayoritas masyarakat meninggalkan kehidupan dari sektor perairan. Alhasil, kota-kota di Kalimantan yang dulunya hidup dari sektor perairan mulai surut dan padam. Suatu indikasi bahwasanya telah terjadi perubahan sosial dan budaya masyarakat di berbagai kota di Kalimantan. Hal tersebut diakibatkan oleh berbagai faktor, seperti modernisasi dan industrialisasi yang berakibat langsung terhadap perubahan lingkungan fisik, perubahan penduduk, sikap dan nilai-nilai, serta kebutuhan yang dianggap perlu.